A FORGOTTEN HERO: JAN MORAWIŃSKI (1907–1949) - Roman Olkowski (Index Copernicus International S.A., 2021)
Notes of a Curator at the National Museum published in 1970 in the second volume of the book Struggle for Cultural Goods is the only generally available testimony to saving the Wilanów historic monuments by Jan Morawiński, a forgotten hero from the times of WW II. Additionally priceless because of Morawiński documenting the looting of 137 paintings belonging to the pre-WW II Branicki collection at Wilanów. The above-mentioned Notes were published by the Państwowy Instytut Wydawniczy after the manuscript kept in the private archive of the author’s daughter Agnieszka Morawińska. The notes, however, resemble pieces of paper torn from a notebook in which an earlier chapter is missing. The missing chapter does exist, yet for unknown reasons was omitted in the two-volume Struggle for Cultural Goods. Warsaw 1939–1945 edited by Prof. Stanisław Lorentz. The present paper is based on Morawiński’s hand-written testimony, supported by archival sources and recollections of his colleagues from the National Museum in Warsaw (MNW). From August 1939 to August 1944, Jan Morawiński, together with others, was involved in saving precious museum exhibits in the Museum building, but also throughout Warsaw. He was involved in packing the historic monuments into crates which were to help them survive the toughest times, and he helped to put out fires at the Museum, risking his own life. Moreover, he rescued the Royal Castle collections during the hardest bombing of Warsaw, transporting them to the storages in Warsaw’s Jerozolimskie Avenue. For his dedication he was awarded the Virtuti Militari Cross of the 5th class by Gen. Juliusz Rómmel. After Warsaw’s surrender, he was assigned Head of MNW’s storerooms and inventories: when Director Lorentz was absent, he acted as his deputy. In the first period of the Nazi occupation he courageously faced German officials. Furthermore, he headed the clandestine action of inventorying and documenting German destructions and plundering. The knowledge amassed in this way was extremely helpful in the restitution of the looted historic monuments, not only museum ones. He also contributed to documenting the destruction of the Warsaw Castle. Imprisoned by the Nazis, he went through Gestapo’s hands at Daniłowiczowska Street in Warsaw. Later on, he became manager of the Museum of Old Warsaw in the Old Town, at the same time acting as a guardian of the Wilanów collection. Following the defeat of the Warsaw Uprising, he participated in the so-called Pruszków Action in whose course he was badly injured.